2019
DOI: 10.15283/ijsc18114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bone Marrow-Derived Mesenchymal Stem Cells on Ischaemic-Reperfused Hearts in Adult Rats with Established Chronic Kidney Disease

Abstract: Background and Objectives Bone marrow-derived mesenchymal stem cells (BM-MSCs) are adult multipotent non-haematopoietic stem cells that have regeneration potential. The current study aimed to detect the ability of BM-MSCs to improve kidney and cardiac functions in adult rats with established chronic kidney disease. Methods Rats were divided into sham-operated control, untreated sub totally nephrectomised and treated sub totally nephrectomised groups. Body weight, kidney… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Group Ib: (BMSCs treated group): Each rat of this group received 0.5 ml of PKH26 labelled MSC suspension in BPS (3x10⁶ cells/ml) for two consecutive days via the tail vein [29] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Group Ib: (BMSCs treated group): Each rat of this group received 0.5 ml of PKH26 labelled MSC suspension in BPS (3x10⁶ cells/ml) for two consecutive days via the tail vein [29] .…”
Section: Methodsmentioning
confidence: 99%
“…Group III (Remedesivir and BMSCs treated group) (n=13 rats): 1 ml of PKH26-labelled MSC suspension in BPS was administered to rats on day 1 following administration of remediesivir for two consecutive days (3x10⁶ cells/ml) IV via tail vein [29] .…”
Section: Methodsmentioning
confidence: 99%
“…The ability of stem cells to restore normal kidney function can be explained by their ability to undergo selective migration into damaged tissues and their ability to express growth factor receptors and chemokines released from organs with inflammatory change ( 7 ). In damaged organs, stem cells have the potential to differentiate into various tissues, such as tubular epithelial cells, mesangial cells of nephrons, podocytes, or glomerular endothelial cells ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…1,6 Besides human MSCs, MSCs have been isolated from different species including mice, rats, rabbits, sheep, pigs, and dogs. [7][8][9][10][11][12] Mesenchymal stem cells (MSCs) are considered of the most promising cells for gene therapy and tissue engineering. [13][14][15][16][17] MSC therapy is poised to establish a new clinical paradigm; although MSCs are originally considered to treat connective tissue defects, preclinical studies 1 revealed potent immunomodulatory properties that prompted the use of MSCs to treat numerous inflammatory conditions.…”
Section: Introductionmentioning
confidence: 99%